A Comprehensive Exploration of Optical Properties of GdAlO3: Cr3+ - Souissi, H.; Kammoun, S.; Dhahri, E.; Pina, J.; Costa, B. F. O.; Brito, A. L. B.; FAUSTO, RUI (Elsevier, 2025)
This study focused on the optical properties of the Cr3+-doped GdAlO3 perovskite, through comprehensive analysis of its photoluminescence spectra. The GdAlO3: Cr3+ perovskite, synthesized by a traditional solid-state process, crystallizes in the orthorhombic Pbnm space group, with Cr3+ ions substituting Al3+ ions in octahedral sites. Photoluminescence excitation and emission spectra of the material were obtained and assigned. The zerophonon lines ZPL of the observed emission and excitation transitions associated with the Cr3+ ions, in the visible range, were determined, and the experimental spectral data were modelled by the Fourier transformation of the autocorrelation function, enabling the calculation of diabatic potential energy profiles for the ground and lowest energy excited states. Crystal field parameters were derived, providing insight into the electronic structure of Cr3+ in the Oh symmetry site. The results highlighted the significant impact of coordination on the electronic structure of Cr3+ ions, with a notably high nephelauxetic effect parameter (h = 1.44), indicating a high degree of covalency in the metal-ligand bonds. Energy transfer from Gd3+ to Cr3+ in GdAlO3: Cr3+ was found to be significant, contributing to the enhancement of the deep-red emission of the compound attributed to the 2Eg(2G) -> 4A2g(4F) d-d transition of Cr3+. Finally, the CIE 1931 chromaticity coordinates of the photoluminescence emission of GdAlO3:Cr3+ were determined, positioning the emission at the boundary of the chromaticity diagram, indicative of its high color purity and potential suitability for red light-emitting display applications.
Keywords: Crystal and ligand fields; GdAlO3 perovskite; Photoluminescence; PLE and PL spectra; Transition metal compounds; UV/Vis.